DETERMINE REGIONAL STRATEGY IN IMPROVING THE COMPETITIVENESS OF AGRICULTURAL COMMODITIES IN GLOBAL MARKETS - Irlan Adiyatma Rum; Jacobus Cliff Diky Rijoly (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2019)
Trade liberalization has affected Indonesian economy. The country success in international trade is truly determined by the regional sectoral competitiveness. The government recognized that agricultural commodities have higher degree of vulnerability to global trade pressures due to weak competitiveness. This study tried to identify the regional strategies that could be taken by the government in improving the competitiveness of agricultural commodity and determine the optimal solution that need to be considered. To determine the position of agricultural competitiveness, calculated Revealed Comparative Advantage (RCA), Revealed Comparative Trade Advantage (RCTA), and Trade Specialization Index (TSI) for some strategic commodities in agricultural Indonesia to export destinations. The results show that Indonesia experienced a decline in their competitiveness in global trade. It has been proved from the comparation over time and with other export countries. This study proposes regional strategy to improve national competitiveness based on their regional competitiveness.